EFEKTIVITAS BANTUAN UNTUK KORBAN BENCANA GEMPA BUMI LOMBOK - DIANTINI, SRI; KENCANA, I PUTU EKA N.; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika, 2019)
On August 2018, an earthquake occurred in North Lombok, West Nusa Tenggara which can be felt from a neighbor region such as West Lombok, Karangasem, and many others. The earthquake caused many casualties and material made many people feel sympathy for the victims of the earthquake. Therefore, many aids and donations came to the affected areas. However, the arrival of aids didn't result in similar perception among victims. The aim of this research is to analyze aid effectiveness of earthquake disaster victims in Lombok, West Nusa Tenggara. In addition, the expectation, realization, and response time of aids will be considered. This research implemented by using partial least square-structural equation modeling (PLS-SEM). This research uses six-first order latent variable, three-second order and one-third order latent variable were built by hierarchical construct model. Data were collected by using questionnaires with 5 likert scale on December 2018 that were distributed directly to 180 victims of earthquake disaster with purposive sampling method. The results show the expectation, realization, and response time regarding the aids for the victims was significant in affecting aid effectiveness and aids of earthquake disaster victims was effective.